1997
DOI: 10.1093/infdis/175.supplement_1.s205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Poliovirus Vaccine Delivery during the 1994 National Immunization Days in Pakistan

Abstract: Pakistan conducted national immunization days (NIDs) for the first time in 1994. To estimate coverage, to evaluate risk factors for failure to be immunized, and to determine the effectiveness of mass media, parents of 1288 children in 714 households in four districts were surveyed after the first NID round. In each district, a high proportion of children (93%-96%) received oral poliovirus vaccine (OPV) during the NID. In three districts, unimmunized or partially immunized children were less likely to receive N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Further, motivation, utilization of primary health centers, the immunization status slightly increased from 19 to 22%; parental knowledge also increases immunization status from 12 to 16.5% [11,15] Although media campaigns also have shown to improve the coverage especially in the NIDs but remains unsatisfactory. [16] A study done at Hyderabad, the second big city of Sindh province after Karachi, showed that the commonest reason for not vaccination or incomplete vaccination was a lack of motivation and careless attitude of parents in 56.6%. Mothers were although aware of its importance but could not find time to take the child to nearby EPI-center or because of the distance of EPI centers in 15%, illness of child in 17%, lack of awareness in 31.29%, no knowledge in 8% and fear of vaccine in 3.4% [17] Therefore more health interventions are needed at the hospital and the community level to ensure immunization in children less than five years of age, by improving parental education, motivating them to vaccinate their children which in turn reduce the underfive mortality [18].…”
Section: Vaccination Status and Factors For Non-vaccination In Childrmentioning
confidence: 99%
“…Further, motivation, utilization of primary health centers, the immunization status slightly increased from 19 to 22%; parental knowledge also increases immunization status from 12 to 16.5% [11,15] Although media campaigns also have shown to improve the coverage especially in the NIDs but remains unsatisfactory. [16] A study done at Hyderabad, the second big city of Sindh province after Karachi, showed that the commonest reason for not vaccination or incomplete vaccination was a lack of motivation and careless attitude of parents in 56.6%. Mothers were although aware of its importance but could not find time to take the child to nearby EPI-center or because of the distance of EPI centers in 15%, illness of child in 17%, lack of awareness in 31.29%, no knowledge in 8% and fear of vaccine in 3.4% [17] Therefore more health interventions are needed at the hospital and the community level to ensure immunization in children less than five years of age, by improving parental education, motivating them to vaccinate their children which in turn reduce the underfive mortality [18].…”
Section: Vaccination Status and Factors For Non-vaccination In Childrmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A review by Nigenda-Lópes covering 40 years showed a variety of reasons: cultural, such as "vaccinations are not important"; psychological, such as "vaccines are unsafe"; social or socioeconomic, such as parents' educational, marital or economic status; structural, such as in relation to vaccine distribution; and transmission-related, i.e. failure to transmit enough information about the diseases and vaccines available.…”
Section: Why Do Children Not Get Vaccinated?mentioning
confidence: 99%
“…2 After one year of age, vaccine failure can affect 7 to 8% of vaccinated children. 4,27,28 OBJECTIVE The aim of this study was to assess the role of communication channels and other risk factors associated with failure to receive the measles vaccine at the right time in the city of São Paulo, Brazil, up to the year 2000.…”
Section: Vaccination Scheme In Brazilmentioning
confidence: 99%
“…This can be accomplished by acquiring representative data of the community from the concerned authorities. The public should also be aware of any upcoming vaccination campaign in their region, so that routine activities can be scheduled in advance for availing vaccination [28]. Girls in the rural areas of Pakistan are not well educated and are mostly confined to their houses due to cultural views.…”
Section: Unawareness and Inequitymentioning
confidence: 99%